ROBOT-ASSISTED RADICAL PROSTATECTOMY WITH DA VINCI XI: OUR INITIAL EXPERIENCE - Deyan Anakievski; Rostislav Marinov; Inna Gocheva; Viktor Nikolov; Pavel Abushev (Peytchinski Publishing, 2022)
During the recent years, prostate cancer becomes a major socio-medical challenge worldwide, as well as in Bulgaria, because of its rising importance and unfavorable impact on human health. Recently we are facing significant theoretical and practical advances in the field of minimally invasive prostate cancer surgery. The last two decades witness a dramatic change in the surgical treatment of most urological diseases with the adventage of a robotic surgical platform. In fact, surgical treatment of prostate cancer has undergone most significant change, thus almost every case nowadays is performed with a robot. The present abstract indicates our initial experience with the use of da Vinci Xi-system in prostate cancer surgery. Materials and methods: 137 robot-assisted radical prostatectomies have been performed in patients with prostate cancer for the period 1 February 2020 / 1 May 2021 in our clinic. Results: The average operative time for the performed operations with minimal blood loss was 160 minutes. Blood transfusion was performed to two patients, whereas no conversion of operations was required in other patients. About half of the patients underwent extended pelvic lymph node dissection due to the high risk for them. Conclusion: Robot assisted radical prostatectomy (RARP) is shown to be an easily performed laparoscopic technique and best practice, compared to the standard open procedure. When analyzing the open approach, certain preliminary studies indicate that robotic prostatectomy has similar outcomes in short-term oncologic control, continence and potency. Initial long-term quality-of-life outcomes have demonstrated priority results for robotic radical prostatectomy, compared to open radical prostatectomy.